Pelatihan Pengembangan Materi Ajar Berbasis Ethno-Discovery Project (EDP) bagi Guru IPA SMP/MTs di Jawa Tengah - Muslimah Susilayati; Fenny Widiyanti (Universitas Mataram, 2025)
This study aims to identify the training needs for developing Ethno-Discovery Project (EDP)-based teaching materials for junior high school science teachers (SMP/MTs) in Central Java and to describe the outcomes of such training. The Participatory Action Research (PAR) method applied in this study emphasizes six key aspects: formative process, system improvement, problem-solving, model analysis, participatory involvement, and critical corporate self-consciousness. Based on the findings and discussion, it can be concluded that the training needs of science teachers at the SMP/MTs level in Central Java include, in order of priority: training in developing teaching materials, developing learning media, developing learning evaluation instruments, and developing lesson plans (RPP). Furthermore, the training on developing EDP-based teaching materials for junior high school science teachers has enhanced their professional, pedagogical, social, and personal competencies. Approximately 95% of the participating science teachers were able to design an outline of EDP-based teaching materials after completing the training. These findings indicate that EDP-based training serves as an effective model for strengthening teachers’ capacity to integrate local wisdom and discovery-based learning into science education, thereby supporting the improvement of instructional quality in junior high schools throughout Central Java.